The Effect of Education and Skills on Unemployment: the Moderation Role of Economic Growth - Ginanjar, Ardhita Eko; Prakoso, Albrian Fiky; Wulandari, Wida; Dewi, Retno Mustika (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
Aspects of community education, namely the average length of schooling (RLS) and Community Vocational Skills (CVS), are important to know community welfare, one of which is seen from the open unemployment rate (TPT). Thisstudy aims to analyze: (1) The relationship between RLS and TPT, (2) The effect of CVS on TPT, (3) The role of economic growth (EG) as a moderator between RLS and TPT, and (4) The role of economic growth (EG) as moderation between CVS and TPT, in Sidoarjo, East Java using 2019-2023 data. Using the Structural Equation Modeling (SEM) method, the findings show that people's vocational skills are the main thing that affects TPT levels. However, the study notes that economic growth failed to moderate the relationship between RLS and CVS on TPT. The role of the government is crucial to improve vocational skills in the form of massive training for prospective workers with related industries.